A Critical Analysis of Sulaiman Layeq’s Literary Life in Afghan Literature - Zabihullah Adabpal; Ramesh Singh Chauhan (LingPoet: Journal of Linguistics and Literary Research, 2023)
This article strives to explore the literary life of a famous and national poet and writer of Afghani literature – Sulaiman Layeq. He, in modern Pashto literature, spent more than eight decades fighting for the reform of Afghan society. He has published about thirteen works both in poetry and prose. His most important work is Chunghar (1962) for which he was awarded the literature prize in Afghanistan. Different sources and e-sources were checked and reviewed, and the collected data were analyzed based the on thematic analysis technique. In the result as one of the major objectives of the study was that Layeq despite being a famous political figure in the Afghan government he was an accepted national and regional Pashto and Dari language short story writer and a revolutionary poet. He was a literary figure both as a modern writer and a social realist. He has been literary critiqued by many literary scholars according to whom he is a splendid, rebelling, and multiethnic poet. He, with a simple and new literary style, was directly addressing what he was supposed to reform through his writings.